2020
DOI: 10.1002/ece3.6862
|View full text |Cite
|
Sign up to set email alerts
|

Unaltered soil microbial community composition, but decreased metabolic activity in a semiarid grassland after two years of passive experimental warming

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 128 publications
2
2
0
Order By: Relevance
“…On the other hand, both temperature and time led to large shifts and increased variability in community structure ( Figure 1D ), with the warmer temperature leading to a higher relative abundance of some bacterial taxa over others ( Figure 4A ; Martiny et al, 2013 ; Isobe et al, 2020 ). These results thus suggest a possible causal relationship between changes in community structure and function, as proposed by others ( Hall et al, 2018 ), and despite such changes being rarely observed ( Rocca et al, 2015 ; Graham et al, 2016 ; Fang et al, 2020 ). While changes in carbon use efficiency have been recently accounted for in state-of-the-art forecasting models ( Allison et al, 2010 ; Sinsabaugh et al, 2013 ), changes in bacterial community structure have not Sulman et al (2018) .…”
Section: Discussionsupporting
confidence: 83%
“…On the other hand, both temperature and time led to large shifts and increased variability in community structure ( Figure 1D ), with the warmer temperature leading to a higher relative abundance of some bacterial taxa over others ( Figure 4A ; Martiny et al, 2013 ; Isobe et al, 2020 ). These results thus suggest a possible causal relationship between changes in community structure and function, as proposed by others ( Hall et al, 2018 ), and despite such changes being rarely observed ( Rocca et al, 2015 ; Graham et al, 2016 ; Fang et al, 2020 ). While changes in carbon use efficiency have been recently accounted for in state-of-the-art forecasting models ( Allison et al, 2010 ; Sinsabaugh et al, 2013 ), changes in bacterial community structure have not Sulman et al (2018) .…”
Section: Discussionsupporting
confidence: 83%
“…On the other hand, both temperature and time led to large shifts and increased variability in community structure (Fig 2d), with the warmer temperature leading to a higher relative abundance of some microbial taxa over others (Fig 4), suggesting some degree of phylogenetically conserved responses (Isobe et al, 2020;Martiny et al, 2013). These results thus suggest a possible causal relationship between changes in community structure and function, as proposed by others (Hall et al, 2018), and despite such changes being rarely observed (Fang et al, 2020;Graham et al, 2016;Rocca et al, 2015). While changes in carbon use efficiency have been recently accounted for in state-of-the-art forecasting models (Allison et al, 2010;Sinsabaugh et al, 2013), changes in microbial community structure have not (Sulman et al, 2018).…”
Section: Discussionsupporting
confidence: 73%
“…Warming exhibits divergent effects on soil fungi in various boreal forest ecosystems, leading to either stimulation or suppression of fungal biomass and activity (Allison & Treseder, 2008; Clemmensen et al, 2013), likely influenced by variations in soil moisture or vegetation among different sites. However, it is worth noting that certain studies have proposed that warming may not considerably affect the abundance or composition of microbial communities (Fang et al, 2020; Schindlbacher et al, 2011). These diverse responses emphasise the need for further research to fully understand how microorganisms respond to climate warming, and especially few studies have focused on the protist communities and their interactions with other microorganisms.…”
Section: Introductionmentioning
confidence: 99%